Handbook on advances in remote sensing and geographic information systems : paradigms and applications in forest landscape modeling - Favorskaya, M. N.; Jain, L. C. (Intelligent systems reference library ;, 2017)
This book presents the latest advances in remote-sensing and geographic information systems and applications. It is divided into four parts, focusing on Airborne Light Detection and Ranging (LiDAR) and Optical Measurements of Forests; Individual Tree Modelling; Landscape Scene Modelling; and Forest Eco-system Modelling. Given the scope of its coverage, the book offers a valuable resource for students, researchers, practitioners, and educators interested in remote sensing and geographic information systems and applications.